THE INFLUENCE OF TRANSFER OF AUTHORITY ON EMPLOYEE WORK EFFECTIVENESS IN THE SHARIA FINANCING SAVE AND LOAN COOPERATIVE "RABIHAH ABADI MAKMUR" EAST OKU - Solikhan Solikhan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The problem faced by the Sharia Financing Savings and Loans Cooperative "Rabihah Abadi Makmur" East OKU is how the influence between the delegation of authority on the effectiveness of the employee's work, the purpose of this study is to determine the effect of the delegation of authority on the effectiveness of the employee's work at the Sharia Financing Savings and Loans Cooperative "Rabihah Abadi Prosperous” East OKU. The hypothesis proposed is that the delegation of authority has a strong effect on the effectiveness of employees' work at the Sharia Financing Savings and Loans Cooperative "Rabihah Abadi Makmur" East OKU. From the calculation results obtained obtained r = 0.772. After consulting with conservative standards to determine whether or not the relationship is close, it turns out that r = 0.772 lies in the distance between 0.600 - 0.799 which is included in the strong correlation. means showing the influence of the delegation of authority on the effectiveness of the work of employees. Then to answer the hypothesis test proposed in the previous chapter has a relationship or not, then it is tested by hypothesis testing and obtained t count = 3.432. While the value of t table at the 95% confidence level for ( n – 2 ) = 1.860. Then it can be seen that the t-count value is 3.432 > 1.860, thus accepted (Ha) and (Ho) rejected. Key Word : Delegation of Authority, Work Effectiveness